2002
DOI: 10.1159/000066174
|View full text |Cite
|
Sign up to set email alerts
|

Increased Detection of 14-3-3 Protein in Cerebrospinal Fluid in Sporadic Creutzfeldt-Jakob Disease during the Disease Course

Abstract: Diagnosis of Creutzfeldt-Jakob Disease (CJD) is based on neurological signs associated with characteristic electroencephalographic activity or detection of 14-3-3 protein in cerebrospinal fluid. However, the time course of 14-3-3 protein release during sporadic CJD is unknown. We report two observations in which the level of the detected 14-3-3 protein increased significantly with time. These preliminary cases suggest that there may be an increased release of 14-3-3 protein during the course of CJD as already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…This observation is in agreement with published single case reports. 10,13,21,37,38 In our analysis, both sensitivity and specificity increased when the results of the second LP were taken into account. The results of a second CSF test might help to exclude CJD, since with time, levels of brain-derived proteins decline in some other conditions, but usually increase further in CJD.…”
Section: Discussionmentioning
confidence: 80%
“…This observation is in agreement with published single case reports. 10,13,21,37,38 In our analysis, both sensitivity and specificity increased when the results of the second LP were taken into account. The results of a second CSF test might help to exclude CJD, since with time, levels of brain-derived proteins decline in some other conditions, but usually increase further in CJD.…”
Section: Discussionmentioning
confidence: 80%
“…Mollenhauer et al [ 7 ] also discussed the difficulties of CJD diagnosis in advanced cases presenting one sCJD case that became 14-3-3 negative in the final stage of the disease. On the other hand, Giraud et al [ 3 ] reported an increase in the levels of 14-3-3 proteins during the course of the disease in a limited number of sCJD cases. Brandel et al [ 2 ] performed a sequential study in iatrogenic CJD, and observed that 14-3-3 was rarely detectable within the first 3 months of the disease but always positive after 7 months associated with aggravation of the disease and the occurrence of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of other brain-derived proteins, such as microtubule-associated tau protein [ 8 ], S100b [ 4 ] or neurone specific enolase (NSE) [ 13 ] have also been reported to be elevated in CSF in CJD. The published data about how the levels of these proteins are modified during the course of disease are contradictory [ 1 3 , 5 7 , 10 , 11 ]. In addition, the time point during the disease, when biochemical markers are expected to have the highest sensitivity, is not well-defined.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive destruction of the brain leads to leakage of 14-3-3 proteins into the cerebrospinal fluid (CSF), which can be detected by ELISA (Kenney et al, 2000;Green et al, 2002) or Western blotting (Hsich et al, 1996;Takahashi et al, 1999). Elevated 14-3-3 levels are found in the CSF of patients with dementia (Burkhard et al, 2001) or suffering from prion diseases (Hsich et al, 1996;Collins et al, 2000;Zerr et al, 2000;Giraud et al, 2002;Geschwind et al, 2003). In this regard, detection of 14-3-3 proteins in CSF is not disease-specific, but rather reflects the process of damaged neurons spilling their proteins into CSF (Pocchiari et al, 2004;Cuadrado-Corrales et al, 2006).…”
Section: Introductionmentioning
confidence: 99%